Factors associated with vaccine-related worry after COVID-19 vaccination: A study of triple vaccinated people in Serbia - Tatjana Gazibara; Verica Jovanovic; Petar Lukic; Vida Jeremic Stojkovic; Marija Milic; Smiljana Cvjetkovic; Jelena Dotlic; Natasa Maksimovic; Maja Sekulic; Gordana Markovic (Elsevier, 2024)
Problem considered: People who accept vaccination can still hold false beliefs about vaccines and COVID-19 pandemic. The purpose of this study was to identify behaviors, misbeliefs, sources of information and trust in institutions associated with vaccine-related worry. Methods: Adults who received the third dose of COVID-19 vaccines at a major national referral center in September and October 2021 were included in this cross-sectional study. Participants filled in a self-reported questionnaire which included statements about uncertainties regarding vaccination and fake news identified in a previous qualitative research. Results: The study included 366 participants (average age 41.6 ± 15.5 years). A total of 35.2% of participants believed in at least one piece of fake news. Of those who did believe in fake news, most (25%) believed that the SARS-CoV-2 was made in a lab. Holding beliefs that COVID-19 vaccines were not investigated enough and that vaccines allow for the injection of nano-technological devices, receiving information about COVID-19 from the Internet and having less trust in health care workers were associated with a higher degree of worry about COVID-19 vaccination. Receiving information from medical journals made people less prone to worry about COVID-19 vaccination. Conclusion: To prevent the spread of false information, it is of paramount importance to have a coordinated system of people and institutions to deliver accurate, clear and compelling information about health-related issues to address false narratives and enhance public trust in health care workers, medicine and science.